Some Properties of Multivalent Functions Associated with a Certain Operator - He, P.; Zhang, D. (Ukrains’kyi Matematychnyi Zhurnal, 2013)
We obtain some subordination and superordination results involving a new operator. By means of the new introduced operator \( C_{p,n}^{λ }(a,c)f(z), \) for some multivalent functions in the open unit disc, we establish the differential sandwich theorem.